2018
DOI: 10.1093/humrep/dey057
|View full text |Cite
|
Sign up to set email alerts
|

FSHB −211 G>T is a major genetic modulator of reproductive physiology and health in childbearing age women

Abstract: Not applicable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…The carriers of AA genotype showed a lower number of oocytes retrieved and a higher consumption of exogenous gonadotropin than GG carriers. As for the FSH β chain polymorphism (rs10835638), a study involving 169 healthy women, and 186 infertile women suggested that this polymorphism is associated with significantly higher FSH and LH levels in both healthy and female infertility patients (33). In this report, the T-allele carriers were found more frequently among idiopathic infertility cases, a fact that could be explained by the influence of this particular polymorphism on FSHR function (26, 34, 35).…”
Section: Unexpected Suboptimal or Low Oocyte Number And Its Associatimentioning
confidence: 99%
“…The carriers of AA genotype showed a lower number of oocytes retrieved and a higher consumption of exogenous gonadotropin than GG carriers. As for the FSH β chain polymorphism (rs10835638), a study involving 169 healthy women, and 186 infertile women suggested that this polymorphism is associated with significantly higher FSH and LH levels in both healthy and female infertility patients (33). In this report, the T-allele carriers were found more frequently among idiopathic infertility cases, a fact that could be explained by the influence of this particular polymorphism on FSHR function (26, 34, 35).…”
Section: Unexpected Suboptimal or Low Oocyte Number And Its Associatimentioning
confidence: 99%
“…It is important to note that the significant association observed for the FSHB gene reconfirms the important role it plays in both male and female fertility. Recently, Rull and colleagues [24] proposed that FSHB -211 G>T variant (association p-value in this study = 2.02 × 10 −5 ) represents a key genetic modulator of circulating gonadotropin, leading to various possible downstream effects on reproductive physiology. The novel genome-wide hit on chromosome 15 identified in this study, rs428022, is an intergenic SNP flanked by PIAS1 and SKOR1, and was additionally mapped to CALML4 in all three mapping strategies.…”
Section: Discussionmentioning
confidence: 51%
“…In females, the T allele decreases the risk of developing endometriosis, delayed age of menopause, and longer menstrual cycles than the G allele 191 . At the same time, other studies found an association between the T allele and the FSH and LH levels, idiopathic infertility, and worst clinical assisted reproduction outcome 192 , 193 . These data indicate a lower transcriptional activity of the T allele of the FSHB promoter SNP 194 , which would modulate the circulating levels of the hormone, thus impacting ovarian response.…”
Section: Recent Advancesmentioning
confidence: 82%